Integrasi Pendidikan Karakter Melalui Pembelajaran Pendidikan Agama Islam di SMA As-Syafiiyah Medan - Rusadi, Bobi Erno (Sekolah Tinggi Agam Islam Sumatera Medan, 2020)
The millennial generation is the continuation of the relay of national and state life. Welcoming Indonesia's golden 1st century of independence in 2045, the Indonesian nation needs a generation that is intellectually intelligent, skilled and has character. This paper aims to analyze the integration of character education through Islamic religious education at SMA Asy-Syafiiyah Medan. The background of this research shows that the age of the students studied is the millennial generation category. This study used a descriptive qualitative approach with a research background in SMA Asy-Syafiiyah Medan. Data were collected by means of observation, interview and documentation study techniques. The results of this study are the integration of character education through learning Islamic Religious Education effectively given to the millennial generation at SMA Asy-Syafiiah Medan, this is marked by 3 integral stages, namely (1) the planning stages, including the presentation of the integration of character education in the syllabus and learning curriculum. ; (2) the stages of implementation, including learning and school culture (climate); and (3) the third stage, namely evaluation. The evaluation in two steps, namely the evaluation of the process and results. Process evaluation is carried out in the learning process, while result evaluation is carried out at the end of the semester.